2021
DOI: 10.1016/j.livsci.2021.104484
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis of the racing line Quarter Horse: Genetic diversity and most influential ancestors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…There was a decrease in EBVs for all traits with advancing equestrian age (Table 4), suggesting that the animals can be selected early for breeding, i.e., immediately after completing 2 years of equestrian age. This approach makes it possible to reduce the long generational intervals (>10 years) of this population [12]; in fact, the generational interval is one of the limiting factors in the genetic improvement of horse breeding programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a decrease in EBVs for all traits with advancing equestrian age (Table 4), suggesting that the animals can be selected early for breeding, i.e., immediately after completing 2 years of equestrian age. This approach makes it possible to reduce the long generational intervals (>10 years) of this population [12]; in fact, the generational interval is one of the limiting factors in the genetic improvement of horse breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic trends have decreased over the last 10 years (2005 to 2014) ( Figure 1 ), a finding that suggests possible stagnation in the genetic evolution of the racing line of the QH breed in Brazil, comparable to that reported for the Thoroughbred breed [ 7 ]. The stagnation and genetic losses observed in the last decade ( Figure 1 ) must be recovered through targeted mating, with an increase in the number of breeding animals with origins different from the ancestors of the QH breed in Brazil, as suggested in the populational study [ 36 ], who observed a genetic bottleneck in the current population of the racing line of the QH breed in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation